2021
DOI: 10.1111/jcmm.16218
|View full text |Cite
|
Sign up to set email alerts
|

Genetic analysis of the CITED2 gene promoter in isolated and sporadic congenital ventricular septal defects

Abstract: Ventricular septal defect (VSD) is the most common congenital heart defect. Previous studies have reported genetic variations in the encoding region of CITED2 highly associated with cardiac malformation but the role of CITED2 gene promoter variations in VSD patients has not yet been explored. We investigated the variation of CITED2 gene promoter and its impacts on gene promoter activity in the DNA of paediatric VSD patients. A total of seven variations were identified by Sanger sequencing in the CITED2 gene pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 32 publications
4
11
0
Order By: Relevance
“…Genomic DNA was extracted from peripheral leukocytes using standard procedure (18). The sequence of the ISL1 promoter was obtained from the GenBank database (NCBI, NG_023040.1) and amplified from human genomic DNA.…”
Section: Sequence Analysismentioning
confidence: 99%
“…Genomic DNA was extracted from peripheral leukocytes using standard procedure (18). The sequence of the ISL1 promoter was obtained from the GenBank database (NCBI, NG_023040.1) and amplified from human genomic DNA.…”
Section: Sequence Analysismentioning
confidence: 99%
“…The promoter is a component of a gene that controls the onset and extent of gene expression, playing a key role in transcriptional regulation. Recently, studies have demonstrated that variants within the promoter region of a gene may be correlated to changes in gene expression levels, leading to disease (de Vooght et al, 2009; Juge et al, 2018; Zheng et al, 2021a; Zheng et al, 2021b).…”
Section: Introductionmentioning
confidence: 99%
“…In humans, variants in CITED2 were identified in patients with congenital heart defects (CHD) such as sinus venosus atrial septal defects, abnormal pulmonary venous return to the right atria, Tetralogy of Fallot, dextrocardia and other ventricular septal defects [ 41 , 43 ], also seen in patients with MYRF variants [ 44 ]. More importantly, several of these variants are localized in the promoter region of CITED2 and have been proven to alter CITED2 transcriptional activity, decreasing their expression [ 41 , 45 ]. Therefore, it is possible that haploinsufficiency of transcription factors of CITED2 , such as MYRF , can influence its expression levels and lead to heart defects.…”
Section: Discussionmentioning
confidence: 99%